2007
DOI: 10.1002/ajmg.a.32037
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of sexual development: A new paradigm

Abstract: The classical paradigm of human and mammalian sexual development, largely based on work of Alfred Jost, depicts the genetic factor(s) that determine(s) sex as influencing only the fate of the gonad. A maleness factor produces testes (Primary Sex Determination). These organs secrete hormones which cause male Secondary Sexual Differentiation. In absence of the maleness factor, by default the gonad becomes an ovary, and the absence of testicular hormones leads to female secondary differentiation. In this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 98 publications
0
31
0
5
Order By: Relevance
“…However, female development is not carried out by default since recent studies suggest that both Y and X sex-chromosomal primary mechanisms of sex determination probably exist [16]. In addition, sex-chromosomal sexdetermining genes can influence not only the development of non-gonadal secondary sexual organs but also of organs outside of the reproductive system, such as brain [16].…”
Section: It's Not All Hormones the Roles Of Sex Chromosomesmentioning
confidence: 99%
“…However, female development is not carried out by default since recent studies suggest that both Y and X sex-chromosomal primary mechanisms of sex determination probably exist [16]. In addition, sex-chromosomal sexdetermining genes can influence not only the development of non-gonadal secondary sexual organs but also of organs outside of the reproductive system, such as brain [16].…”
Section: It's Not All Hormones the Roles Of Sex Chromosomesmentioning
confidence: 99%
“…However, female development is not carried out by default, since recent studies suggest that both Y and X sex-chromosomal primary mechanisms of sex determination probably exist (75) . In addition, sex-chromosomal sex-determining genes can influence not only the development of nongonadal secondary sexual organs but also of organs outside the reproductive system, such as the brain (75) . In order to accommodate recent findings it has been proposed that sexual dimorphism precedes gonadal development.…”
Section: Transduction Of Environmental Signals To the Epigenetic Machmentioning
confidence: 99%
“…Recently, it was found that the sexual dimorphism between male and female cells in their response to chemical exposure to either ethanol or camptothecin apparently occurred at fetal stages that preceded the production of sex hormones and, accordingly, could be directly attributed to a sex chromosome effect [93,94] . Sex-determining genes on sex-chromosomes can influence not only the development of non-gonadal secondary sexual organs but also of organs outside of the reproductive system, such as brain [95] . Indeed, at the level of the whole body, the sex-chromosomes are crucial for establishment of sex-dimorphism of cellular functions [42] .…”
Section: I�'�� ���� ��� �����������: R������ ��� ����X ��������������mentioning
confidence: 99%